Ameliorative properties of aqueous extract of Ficus thonningii on erythrocyte osmotic fragility induced by acetaminophen in Rattus norvegicus - Victor Masekaven Ahur; Yahaya Adenkola Adenkola; Saganuwan Alhaji Saganuwan; ob Terungwa Ikye-Tor (Veterinary Research Forum, 2013)
In vitro antioxidant and erythrocyte protecting activities by aqueous extract of Ficus thonningii leaves on blood cells were studied in acetaminophen treated rats. The extract was safe at limit dose of 5000 mg kg-1body weight. The extract demonstrated dose dependent antihemolytic effect at dose levels between 50 and 200 mg kg-1 body weight. The lowest antihemolytic effect was observed at dose level of 200 mg kg-1 body given the lowest percentage hemolysis of 10.53 ± 1.76%, whereas the highest percentage hemolysis at dose level of 50 mg kg-1 was 29.02 ± 7.45%. Hematology revealed erythrocytosis at dose levels of 100 and 200 mg kg-1 body weight. Hyper-globinemia and lymphocytopenia were observed at dose levels of 100 mg kg-1 and 200 mg kg-1, respectively. The extract effectively showed scavenging activity on a stable oxidative radical diphenylpicrylhydrazyl (DPPH) and a significant ferric reducing antioxidant power (FRAP) activity. The plausible erythrocyte membrane protective effect may be due to its free radical scavenging activity and hence the extract can be used to improve hematological parameters and ameliorate oxidative stress.